A prospectus for bilingual early reading instruction - Taraban, Roman; Meza, Isabel; Lernatovych, Oksana; Zasiekin, Serhii; Saraff, Sweta; Biswal, Ramakrishna (East European Journal of Psycholinguistics, 2023)
In this paper, we describe a framework for bilingual decoding instruction, with a call for collaborators. Decoding is the ability to apply knowledge of letter-sound correspondences to pronounce words. We adopt a standard phonological approach for early instruction that could be expanded to include practice with constructive morphemes, like prefixes and suffixes, and reading for meaning. Decades of research have shown that word decoding is a bottleneck in reading comprehension. Unless children develop sight-word reading capabilities, comprehension of texts is severely hampered. The present approach draws on children’s spoken vocabulary knowledge in their native language as a bridge to decoding in a second language. The goal is to develop a tutoring system that draws on current and forthcoming multimedia technologies, and to implement the system in multilingual countries, e.g.: USA, India, Ukraine and across national borders. As a starting point, the authors will use a web platform https://ethicalengineer.ttu.edu designed in 2017 by the USA, Indian, and Ukrainian collaborators, several of them being co-authors of this paper, as a model for the new website for reading instruction. The Ethical Engineer website demonstrates one mechanism through which instructors can reach out to establish connections within and outside their native country around topics and issues of common interest and support educator cooperation and research development. The new model hopes to achieve success comparable to that of the Ethical Engineer. Using computer-based instruction allows for empirical testing of teaching methods, thereby optimizing the educational process. It is important to take advantage of this to ensure the most effective methods are used in early reading instruction for children. Disclosure Statement No potential conflict of interest was reported by the authors. * Corresponding author: Roman Taraban, 0000-0002-1815-4687 roman.taraban@ttu.edu